Electrochemical Deposition and Characterization of Copper Indium Disulfide Semiconductor Thin Films - Teo, Sook Liang (2011)
Copper indium disulfide (CuInS2) has attracted much interest as absorber layer in photovoltaic cellapplications because of its direct band gap energy of ~1.5 eV, high conversion efficiency, high absorption coefficient and free from hazardous chalcogenides, selenium or tellurium. In this work, three electrochemical deposition techniques were used in the preparation of CuInS2 thin films namely potentiostatic deposition, pulse electrodeposition and potentiodynamic deposition. CuInS2 thin films were deposited onto fluorine doped tin oxide coated glass (FTO) from deposition bath comprised of Cu-EDTA, In2(SO4)3 and Na2S2O3, and the pH was adjusted to ~2.30 by using sulfuric acid. A three electrode-cell was used, where Ag/AgCl/3M NaCl as the reference electrode, FTO as the working electrode and platinum wire as the counterelectrode. Cyclic voltammetry was used to investigate the probable range of deposition potential and the potential range obtained was at -0.80 V to -1.00 V. Deposition parameters such as potential (-0.85 V to -1.20 V), time (10 min to 50 min), pulse magnitude (-0.85 V to -1.20 V), duty cycle (10% to 90%), scan rate (5mV/s to 40 mV/s), potential cycling (5 cycles to 50 cycles), concentration of CuSO4 (0.004 M to 0.020 M), concentration of In2(SO4)3 (0.004 M to 0.020 M) and annealing temperature (250 oC to 400 oC ) were studied. X-ray diffraction (XRD) patterns showed that the deposited CuInS2 films were polycrystalline with tetragonal structure at hkl planes of (200), (112) and (204). The photoelectrochemical (PEC) properties of the films were evaluated using linear sweep photovoltammetry by intermittently illuminating the samples which was immersed in 0.01 M Na2S2O3 electrolyte with a halogen lamp (120 V 300 W). Photocurrent was observed due to cathodic reaction involving generated minority carriers of electrons. Thus, CuInS2 is a p-type semiconductor as deposited in this study. The XRD and PEC results suggested the suitable electrolyte bath composition for CuInS2 deposition was 0.01 M Cu-EDTA, 0.01 M In2(SO4)3 and 0.40 M Na2S2O3. A smooth adherent film was obtained at potential -1.00 V with deposition time of 30 min in potentiostatic deposition. While for pulse electrodeposition, pulse potential of -1.00 V at 50% duty cycle showed good PEC behaviour. Besides, for potentiodynamic deposition, a significant PEC effect was obtained at potential range of -0.40 V to -1.00 V with scan rate of 25 mV/s for 20 cycles. Annealing improved the film crystallinity, but caused the formation of impurity phases and resulted in poor photoresponse. The band gap energy of samples prepared by these techniques was found to be within 1.20-1.40 eV with indirect transition. The surface roughness mean squares of 218.60 nm, 74.73 nm and 93.30 nm were respectively obtained for potentiostatic, pulse and potentiodynamic deposition as examined using atomic force microscopy. The morphology of the films was further studied using scanning electron microscopy (SEM), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). Based on SEM cross sectional images, the thicknesses of potentiostatic, pulse and potentiodynamic deposited films were estimated to be 5.06 μm, 1.55 μm and 3.32 μm respectively. From FESEM and TEM, the obtained grain shape varied from spherical to worm like for potentiostatic, pulse and potentiodynamic deposition. The crystallite sizes estimated from XRD, FESEM and TEM were 24.27-29.59 nm for potentiostatic technique, 40.45-47.08 nm for pulse electrodeposition and 31.93-36.41 nm for potentiodynamic deposition. The Cu:In:S compositions of the films were evaluated using energy dispersive X-ray analysis which resulted in 1.0:1.1:2.1, 1.1:1.0:1.8 and 1.2:1.0:1.7 respectively for potentiostatic, pulse and potentiodynamic deposition. The reasons for these compositional trends are elaborated in the text. Cyclic voltammetry was run to investigate the electrochemical properties of the films in various supporting electrolytes (NH4Cl, (NH4)2SO4, KCl, K2SO4), concentration (0.01 M to 2.00 M), pH (1.35 to 10.00) and potential cycling (1 cycle to 10 cycles). Cu2+/Cu+ and Cu+/Cu0 redox peaks were observed for all films. The film deposited using potentiostatic technique showed a good electrochemical stability compared to other techniques. Chronocoulometry study showed potentiostatic deposited film had a high surface charge of 0.115 Coulomb.